HUBUNGAN POLA ASUH ORANG TUA DENGAN KEJADIAN STUNTING PADA BALITA DI PAUD MELATI KECAMATAN SEMENDAWAI TIMUR KABUPATEN OKU TIMUR TAHUN 2023 : HUBUNGAN POLA ASUH ORANG TUA DENGAN KEJADIAN STUNTING PADA BALITA DI PAUD MELATI KECAMATAN SEMENDAWAI TIMUR KABUPATEN OKU TIMUR TAHUN 2023 - Hanik Khairun Nisa (PROFESSIONAL HEALTH JOURNAL, 2023)
Introduction : Stunting is a condition of failure to thrive in children under five years of age due to chronic malnutrition so that children are too short for their age. Factors that cause stunting are maternal factors and poor parenting, especially in the behavior and practice of feeding their children. Parenting is very closely related to the growth and development of children, where children really need an adequate supply of food and nutrition. The World Health Organization (WHO) states that the prevalence of stunting under five is still a public health problem. Purpose : This study aims to determine the relationship between parenting styles. parents with the incidence of stunting in toddlers. Methods : The research design used in this study was analytic with a cross-sectional approach using primary data by measuring the height of toddlers. Sampling was carried out at Early Childhood Education Melati, East Semendawai District, East Oku Regency. The sample used in this study was 30 people who met the inclusion criteria. Data analysis using Chi Square. Results : The results of this study are that there is a relationship between parenting style and the incidence of stunting in toddlers in Early Childhood Education, Semendawai Timur District, East Oku Regency with a p-value = 0.000. Conclusion : From the results of this study it can be concluded that the parenting style applied by parents can influence the occurrence of stunting.